How accurate are your simulations? Effects of confined aqueous volume and AMBER FF99SB and CHARMM22/CMAP force field parameters on structural ensembles of intrinsically disordered proteins: Amyloid-β42 in water. (1st January 2017) - Weber, Orkid Coskuner; Uversky, Vladimir N.
ABSTRACT: Amyloid-β42 (Aβ42 ) is an intrinsically disordered peptide intimately related to the pathogenesis of several neurodegenerative diseases. Molecular dynamics (MD) simulations are extensively utilized in the characterization of the structures and conformational dynamics of intrinsically disordered proteins (IDPs) including Aβ42, with AMBER and CHARMM parameters being commonly used in these studies. Recently, comparison of the effects of force field parameters on the Aβ42 structures has started to gain significant attention. In this study, the structures of Aβ42 are simulated using AMBER FF99SB and CHARMM22/CMAP parameters via replica exchange MD simulations utilizing a widely used clustering algorithm. These analyses show that the structural properties (extent and positioning of the elements of secondary and tertiary structure), radius of gyration values, number and position of salt bridges are extremely dependent on the chosen force field parameters notably with the usage of clustering algorithms. For example, predicted secondary structure elements, which are of the great importance for better understanding of the molecular mechanisms of neurodegenerative diseases, deviate enormously in models generated using currently available force field parameters for proteins. Based on the derived models, chemical shift values are calculated and compared to the experimentally determined data. This comparison revealed that although both force field parameters yield results in agreement with experiments, the obtained structural properties were rather different using a clustering algorithm. In other words, these results show that the predicted structures depend heavily on the force field parameters. Importantly, since none of the force field parameters currently utilized in MD studies were developed specifically taking into account the disordered nature of IDPs, these findings clearly indicate that new force field parameters have to be developed for IDPs considering their rapid flexibility and dynamics with high amplitude. Furthermore, molecular simulations of IDPs are typically conducted using one water volume. We show that the confined aqueous volume impacts the predicted structural properties of Aβ42 in water. Although up to date, confined aqueous volume effects have been ignored in the MD simulations of IDPs in water, our data indicate that these effects have to be taken into account in predicting the structural and thermodynamic properties of disordered proteins in solution.